Penerapan Media Wordwall untuk Meningkatkan Minat Belajar Matematika pada Peserta Didik Kelas V Sekolah Dasar - Lulud Rahmawati; Vivi Rulviana; Rakini Rakini (Journal Innovation In Education, 2024)
In order to increase the learning interest of class V students of SDN 02 Taman Kota Madiun in learning mathematics about types of angles through the use of wordwall learning media is the purpose of this study. This study is a Classroom Action Research (CAR) which is carried out in 2 cycles with each cycle consisting of several stages, namely the planning, implementation, observation, and reflection stages. This study used research subjects, namely 10 class V students of SDN 02 Taman Kota Madiun. Observations, tests and documentation were used to collect data in this study. In this study, the results obtained stated that in cycle 1 the average score of learning outcomes using wordwall learning media was 64% in classical completeness. Meanwhile, when cycle 2 the average score of learning outcomes using wordwall learning media increased by 86% with very good completeness. Therefore, it can be concluded that students' learning interest in learning mathematics on the material of types of angles in class V students of SDN 02 Taman Kota Madiun can increase with the application of wordwall media.